MASTERING LISTENING COMPREHENSION AT ESP CLASSES USING TED TALKS - Iryna Humeniuk; Oksana Kuntso; Nadiia Popel; Yuliia Voloshchuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The paper demonstrates the results of the experimental research conducted during the first semester of the academic year 2020/21, including the remote learning period due to the Covid19 pandemic situation, at the lessons of English for Specific Purposes (ESP) (with students of Specialties 208 "Agrarian Engineering" and 141 "Electrical Engineering and Energy") at the State Agrarian and Engineering University in Podilia, Kamianets-Podilskyi, Ukraine. The research basically analyses how TED (Technology, Entertainment, and Design) Talks impact university students' listening comprehension and speaking skills. Online study support for ESP was personally created by the educators as a four-credit course due to ECTS in the Moodle Learning Management System (LMS) with the application of TED Talks, which was used for study purposes on the B1 level. The research sample is represented by 50 students majoring in Agrarian Engineering and 50 students majoring in Electrical Engineering and Energy, all of them enrolled in the mandatory subject of ESP. The subjects (students) were divided into the experimental and control groups. At the beginning of the course, the students wrote the pre-test, for their start level to be evaluated, and at the end of the semester - the post-test was done to check the achievements and probable benefits of TED Talks. The experiment results demonstrated the improvement of both groups while it was proved statistically that the experimental group showed better outcomes both in listening comprehension and speaking skills respectively. The questionnaires, distributed among the students, consisted of 5 questions, where they expressed their personal opinions about the e-learning process, and according to which the TED Talks influence on their listening and speaking skills was evaluated. The feedback of the questionnaires proved that the students mostly had a positive attitude concerning engaging TED Talks into the learning process, especially those who were involved in the experiment.